PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN PARTISIPASI AKTIF SISWA KELAS X-4 SMAN 7 MALANG PADA MATERI SISTEM KOMPUTER - Anwar, Khoirul; Prasetya, Didik Dwi; Setiawan, Ahmad Yusuf (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the effectiveness of the Think-Pair-Share (TPS) cooperative learning model in enhancing the conceptual understanding and active participation of tenth-grade students at SMAN 7 Malang in the topic of Computer Systems. The research method employed a quasi-experimental design with a pretest-posttest control group. The sample consisted of 34 students divided into experimental and control groups. The research instruments included a conceptual understanding test and an active participation questionnaire. The analysis results revealed that the experimental group receiving TPS-based instruction showed a more significant improvement in conceptual understanding and active participation compared to the control group. The TPS model proved effective in creating a collaborative learning environment, fostering student engagement, and strengthening conceptual mastery in information technology-related subjects.